2014
DOI: 10.1111/zoj.12206
|View full text |Cite
|
Sign up to set email alerts
|

Systematics of the Southeast Asian mongooses (Herpestidae, Carnivora): solving the mystery of the elusive collared mongoose and Palawan mongoose

Abstract: Although recent molecular studies have clarified the phylogeny of mongooses, the systematics of the Southeast Asian species was incomplete as the collared mongoose Urva semitorquata and some debatable taxa (Hose's mongoose, Palawan mongoose) were missing in the analyses. We sequenced three mitochondrial (cytochrome b, ND2, control region) and one nuclear (beta-fibrinogen intron 7) fragments of the Southeast Asian mongooses to clarify the systematic position of the different species and populations occurring in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
7
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 31 publications
2
7
0
Order By: Relevance
“…The Mentawai Islands have been separated from Sumatra at least since the Mid-Pleistocene and might have remained separated despite the sea level fluctuations of the Late Pleistocene (Voris 2000;. The Cytb distance of the Siberut Island individual to other banded civet populations ranged from 4.7 to 5.5%, which is close to the divergence found between other small carnivore species (Veron et al 2007(Veron et al , 2015a(Veron et al , 2015c; our nuclear data also confirmed this strong divergence. Two subspecies have been described from the Mentawai Islands: Hemigalus derbyanus minor Miller, 1903 (South Pagai Island) andH.…”
Section: Discussionsupporting
confidence: 73%
See 3 more Smart Citations
“…The Mentawai Islands have been separated from Sumatra at least since the Mid-Pleistocene and might have remained separated despite the sea level fluctuations of the Late Pleistocene (Voris 2000;. The Cytb distance of the Siberut Island individual to other banded civet populations ranged from 4.7 to 5.5%, which is close to the divergence found between other small carnivore species (Veron et al 2007(Veron et al , 2015a(Veron et al , 2015c; our nuclear data also confirmed this strong divergence. Two subspecies have been described from the Mentawai Islands: Hemigalus derbyanus minor Miller, 1903 (South Pagai Island) andH.…”
Section: Discussionsupporting
confidence: 73%
“…Our results suggest that there have been independent connections between Borneo and Sumatran populations, and between Borneo and Peninsular Malaysian populations (in this study represented by an individual from Penang Island, which is very close and connected to the NW coast of Peninsular Malaysia). Although Peninsular Malaysia and Sumatra have been connected frequently during glacial periods, the banded civet individuals from these two areas did not form a monophyletic group in our analyses, whereas a close relationship and low differentiation of populations from Sumatra and Peninsular Malaysia have been found in many other mammals, such as rodents, macaques, palm civets and mongooses (Gorog et al 2004;Ziegler et al 2007;Patou et al 2010;Veron et al 2015a). Possible explanations for these findings would be independent dispersals during periods of lower sea levels (e.g., Last Glacial Maximum), or that banded civets were transported from one area to another, as has been suggested for some other civet species (Veron et al 2014(Veron et al , 2015c, although there is no evidence that this has ever occurred for the banded civet.…”
Section: Discussionmentioning
confidence: 59%
See 2 more Smart Citations
“…Considering the criteria for mammal species recognition, specifically the level of Cytb divergence (>5%, Baker & Bradley, ; >1.5%–2.5%, Tobe, Kitchener, & Linacre, ), on the basis of current data, it is best to consider these genera as monotypic. Moreover, while FGB has been proven to vary between species of mammals (e.g., Bezerra et al., ), and especially in Carnivora (e.g., Veron, Patou, Tóth, Goonatilake, & Jennings, ; Veron et al., 2015), it showed no or very little variation among Galidiinae genera.…”
Section: Discussionmentioning
confidence: 99%